Nonlinear Dynamic Response and Vibration of 2D Penta-graphene Composite Plates Resting on Elastic Foundation in Thermal Environments - Nguyen, Dinh Duc (H. : ĐHQGHN, 2019)
This research demonstrates an analytical method for investigation vibration and dynamic response of plates structure which made from 2-Dimensional (2D) penta-graphene. The density functional theory is used to figure out the elastic modulus of single layer penta-graphene. The classical plate theory is applied to determine basic equations of 2D penta-graphene composite plates. The numerical results obtained using the Bubnov-Galerkin method and Rung-Kutta method. The results in this research showed high agreement when it is compared with the other study. The results demonstrate the effect of shape parameters, material properties, foundation parameters, the mechanical load on the nonlinear dynamic response of 2D penta-graphene plates. One of the highlights of this study was to investigate the effect of the thermal environment on the behavior of 2D penta-graphene plates.